Analisis Proses Pembentukan Biogas dari Campuran Limbah Ikan, Kotoran Sapi dan Eceng Gondok (Eichhornia Crassipes) - Dwityaningsih, Rosita; Rahayu, Theresia Evila P.S.; Handayani, Murni; Mardiyana, Mardiyana (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
One of the biomass that can be used for making biogas is fish waste. Based on the research, fish waste has a small c / n ratio so it requires mixing with other organic materials that have a higher c / n ratio. The addition of water hyacinth and cow dung will increase the c / n ratio in the anaerobic process to make biogas. The aim of this research is to analyze the process anaerobically of biogas formation from a mixture of fish waste, cow dung, and water hyacinth. Biogas is made with a variation composition of cow dung (D1), a mixture of cow dung, water hyacinth, and fish waste (D2), and a mixture of cow dung and fish waste (D3).) The Variation ratio of each composition is 1: 0: 0; 5: 1: 1 and 2: 0: 1. The results are the value of volatile solid and total solid for each composition of D1, D2, D3 was 33,600 mg / L, 34,800 mg / L, 33,000 mg / L. Value of Total Solid D1, D2, D3 are 121,800 mg / L, 146,200 mg / L, 174,600 mg / L. Fermentation process lasts for 1 month at a temperature 25oC-33oC and pH 6-7. The rates of degradation of organic compounds for D1, D2, D3 are 0.0058/day; 0.0439/day and 0.0052/day.